A review on properties, challenges and commercial aspects of eco-friendly biolubricants productions. (December 2022) - Ahmad, Uzair; Naqvi, Salman Raza; Ali, Imtiaz; Naqvi, Muhammad; Asif, Saira; Bokhari, Awais; Juchelková, Dagmar; Klemeš, Jiří Jaromír
Abstract: Lubricants operate as antifriction media, preserving machine reliability, facilitating smooth operation, and reducing the likelihood of frequent breakdowns. The petroleum-based reserves are decreasing globally, leading to price increases and raising concerns about environmental degradation. The researchers are concentrating their efforts on developing and commercializing an environmentally friendly lubricant produced from renewable resources. Biolubricants derived from nonedible vegetable oils are environmentally favorable because of their non-toxicity, biodegradability, and close to net zero greenhouse gas emissions. The demand for bio lubricants in industry and other sectors is increasing due to their non-toxic, renewable, and environmentally friendly nature. Good lubrication, anti-corrosion, and high flammability are characteristic properties of vegetable oils due to their unique structure. This study presents several key properties of nonedible oils that are used to produce lubricants via the transesterification process. Bibliometric analysis is also performed, which provides us with a better understanding of previous studies related to the production of bio lubricants from the transesterification process. Only 371 published documents in the Scopus database were found to relate to the production of bio lubricants using the transesterification process. The published work was mostly dominated by research articles (286; 77.088%). Significant development can be seen in recent years, with the highest occurrence in 2021, reaching 68 publications accounting for 18.38% of the total documents. In the second step, (i) the authors with the most number of publications; (ii) journals with the most productions; (iii) most productive countries; and (iv) the authors' most frequently used keywords were evaluated. These results will provide a pathway for researchers interested in this field. Lastly, recommendation is made on research gaps to device possible strategies for its commercialization. Graphical abstract: Image 1 Highlights: Synthesis of bio-lubricant from non-edible oils are critically analyzed. Bibliometric analysis revealed impact in terms of top authors, journals, keywords. Recommendations for bi-lubricant commercialization are suggested.